FDTD simulation of radiation characteristics of half-volume HEM and TE-mode dielectric resonator antennas. - O'Keefe, S.G (IEEE Transactions on antennas and propagation)
Cylindrical and rectangular dielectric resonator antennas (DRAs) using HEM11δ, TE11δ, and TE01δ mode were examined to see the radiation pattern, impedance, field distribution and resonant frequency that were achieved when the DRAs were bisected through an image plane by a conducting sheet. The resultant half DRAs are smaller in volume and have a more directional radiation pattern. The elevation angle of maximum radiation was lowered in some cases. Finite-difference time-domain simulation techniques were used